Ecological Approach towards Reclaiming Mined Ecosystem - Soni, P.; Vasistha, H. B.; Kumar, Om (Indian Forester, 1989)
Present paper emphasizes the role of ecological approach in restoring the degraded mined ecosystem. The four important steps for an effective eco-restoration programme are (i) assessment of The problems, (ii) ecological maintainance of essential processes, (iii) preservation of genetic diversity and (iv) sustainable utilization of species and ecosystems. A case study of eco-restoration of Durmala rock phosphate mine has been presented which shows that after four years of reclamation, the area stabilizes and provides bospitable environment for bumans as well as animal species of birds, reptiles, rabbits etc.